DAYA TERIMA DAN ANALISIS KANDUNGAN GIZI COOKIES BERBASIS TEPUNG DAUN KELOR (Moringa Oleifera L.) DAN TEPUNG KACANG MERAH (Phaseolus Vulgaris L.) - Erniyanti, Erniyanti; ansharullah, ansharullah; Sadimantara, Muhammad Syukri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2019)
ABSTRACTThe purpose of this study was to determine the effect of cookies formulation of Moringa leaves (moringa oleifera L.) and red bean flour (Phaseolus vulgaris L.) on the organoleptic values and nutritional value. This study used a completely randomized design (CRD) consisting of 6 treatments. The variables observed consisting of organoleptic characteristics (color, flavor and texture) and nutritional value (moisture content, ash content, protein content, fat content and carbohydrate content). Water, ash, protein, fat and carbohydrate contents of selected cookies were namely 5.82%, 1.41%, 17.03%, 13.27% 62.38%, respectively. The more addition of Moringa leaf flour and red bean flour had an effect on the increasing of moisture, ash, protein, and fat contents. Based on organoptic assessment, can be accepted (preferred) by panelists. Keywords: Moringa Leaf Flour, Red Bean Flour, Cookies ABSTRAKTujuan pnelitian ini yaitu untuk mengetahui pengaruh formulasi cookies tepung daun kelor (moringa oleifera L.) dan tepung kacang merah (Phaseolus vulgaris L.) terhadap nilai organoleptik dan kandungan nilai gizi. Penelitian ini menggunakan rancangaan acak lengkap (RAL) yang terdiri 6 perlakuan. Variabel yang diamati terdiri dari karakteristik organoleptik: warna, aroma rasa dan tekstur dan nilai gizi (kadar air, kadar abu, kadar protein, kadar lemak dan kadar karbohidrat). Kadar air, kadar abu, kadar protein, kadar lemak dan karbohidrat cookies terpilih berturut-turut yaitu 5.82%, 1,41%, 17.03%, 13.27% 62.38%. Semakin banyak penambahan tepung daun kelor dan tepung kacang merah maka berpengaruh terhadap peningkatan kadar air, kadar abu, kadar protein, dan kadar lemak. Berdasarkan penilaian organoptik, cookies dapat diterima (disukai) oleh panelis.Kata Kunci: Tepung Daun Kelor, Tepung Kacang Merah, Cookies.